2007
DOI: 10.1097/opx.0b013e3180339f81
|View full text |Cite
|
Sign up to set email alerts
|

Variable Responses of Acanthamoeba Strains to Three Multipurpose Lens Cleaning Solutions

Abstract: Findings for individual MPS complement previous work with other methods. This study has also identified that environmental strains vary in their sensitivity to disinfecting solutions. Overall, Acanthamoeba genotypes T3, T5, and T11 from the environment were more resistant than the T4 isolates from the cornea and beach. This resilience supports previous work on temperature tolerance, in which T3 and T5, and T11 acanthamoebae grew in temperatures up to 41 degrees C. Investigators should therefore consider the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…Further complicating the issue are experimental animal and tissue culture models that have shown T5 isolates to be capable of a high degree of pathogenicity (33,34). Additionally, studies comparing T4 and T5 resistance to multipurpose contact lens cleaning solutions, interestingly, show that the T5 genotype possesses a better resistance (16,27). It is possible that the majority of T5 Acanthamoeba isolates may not be pathogenic to humans, but as the number of people that wear contact lenses continues to grow, the risk of encountering pathogenic T5 isolates may increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further complicating the issue are experimental animal and tissue culture models that have shown T5 isolates to be capable of a high degree of pathogenicity (33,34). Additionally, studies comparing T4 and T5 resistance to multipurpose contact lens cleaning solutions, interestingly, show that the T5 genotype possesses a better resistance (16,27). It is possible that the majority of T5 Acanthamoeba isolates may not be pathogenic to humans, but as the number of people that wear contact lenses continues to grow, the risk of encountering pathogenic T5 isolates may increase.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that have determined genotypes of Acanthamoeba strains from AK and contact lens/cases each identified the presence of the T3 genotype, which, based on environmental distribution, is less prevalent than T5 (5,7,37,38). Also, like T5 isolates, T3 isolates can show more resistance to multipurpose contact lens cleaning solutions than do isolates of the T4 genotype (27). Understanding what makes T4 more virulent to humans is an important area of study.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies comparing the T4 and T5 genotypes for resistance to multipurpose solutions, curiously, showed that the T5 genotype has a higher resistance (Hiti et al 2002;Shoff et al 2007). Only isolates of the T2, T3, T4, T6, T11 (Walo- (Spanakos et al 2006;Iovieno et al 2010) genotypes have been associated with keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Shoff et al 51 in 2007 theorized that because Acanthamoeba are carried to the eye attached to the SCL, the disinfection challenge should consist of trophozoites or cysts attached to an agar surface covered with bacteria. In their research, the SCL test product (1.0 mL) was inoculated with a 2 ϫ 2 ϫ 4 mm agar block cut from the amoeba non-nutrient agar-Escherichia coli culture containing a microscopically observed estimate of Acanthamoeba cells and the control was a single agar block with cells in saline.…”
Section: Trophozoites/cysts Attached To Agar Methodologymentioning
confidence: 99%